2010
DOI: 10.1016/j.molcel.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the MMS22L-TONSL Complex that Promotes Homologous Recombination

Abstract: Budding yeast Mms22 is required for homologous recombination (HR)-mediated repair of stalled or broken DNA replication forks. Here we identify a human Mms22-like protein (MMS22L) and an MMS22L-interacting protein, NFκBIL2/TONSL. Depletion of MMS22L or TONSL from human cells causes a high level of double-strand breaks (DSBs) during DNA replication. Both proteins accumulate at stressed replication forks, and depletion of MMS22L or TONSL from cells causes hypersensitivity to agents that cause S phase-associated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 39 publications
4
125
0
Order By: Relevance
“…S2B). In this regard, TONSL is already known to participate in the repair of collapsed or stalled replication forks (Duro et al 2010;O'Connell et al 2010;O'Donnell et al 2010;Piwko et al 2010), which is also a known BRCA1 function (Pathania et al 2011;Schlacher et al 2012). However, as shown below, we found that TONSL may also participate in the response to transcription-associated damage.…”
Section: Genetic Interaction Between Tonsl and Brca1supporting
confidence: 55%
“…S2B). In this regard, TONSL is already known to participate in the repair of collapsed or stalled replication forks (Duro et al 2010;O'Connell et al 2010;O'Donnell et al 2010;Piwko et al 2010), which is also a known BRCA1 function (Pathania et al 2011;Schlacher et al 2012). However, as shown below, we found that TONSL may also participate in the response to transcription-associated damage.…”
Section: Genetic Interaction Between Tonsl and Brca1supporting
confidence: 55%
“…These include RAD51AP1 (Wiese et al 2007) and TONSL/MMS22L (Duro et al 2010, O'Donnell et al 2010. Further analysis will shed more light on the possible interplay between these proteins and HR mechanisms underlying disorders like FA or HBOC.…”
Section: C-terminal Rad51 Binding Sitementioning
confidence: 99%
“…Second, a series of studies suggests a requirement for PARP1 to help resolve stalled replication forks (38,39), which are produced upon treatment with topo I poisons (16,17,40,41). Whether PARP1 acts by modulating WRN helicase (42,43) or recruiting MRE11 (39,44) or both is unclear.…”
mentioning
confidence: 99%